GOOD CORPORATE GOVERNANCE IN ZIS MANAGEMENT: A QUALITATIVE ANALYSIS OF BAZNAS BANYUMAS BASED ON PSAK 109 AND ZAKAT CORE PRINCIPLES - Amara Widya Prastika; Widia Saranti; Metiya Fatikhatur Riziqiyah (Jurnal Akuntansi Syariah (JAkSya), 2026)
This study analyzes the implementation of Good Corporate Governance (GCG) principles in managing zakat, infaq, and shadaqah (ZIS) at BAZNAS Banyumas Regency. The research fills a gap by moving beyond conventional ZIS management studies to incorporate an assessment based on sharia accounting standards (PSAK 109) and specific, measurable governance indicators. The practical contribution lies in providing evidence-based input for strengthening the institution's internal control and transparency policies. Using a qualitative descriptive-comparative approach with secondary data from the 2023 financial report and the 2024 audited report, practices are compared against GCG principles and PSAK 109. The findings reveal that BAZNAS Banyumas has effectively implemented accountability and responsibility, reflected in the zakat fund's Allocation to Collection Ratio (ACR) of 90.88%, which falls into the highly effective category. Nevertheless, gaps persist in information transparency, particularly regarding the narrative disclosure of accounting policies, and an initial finding concerning the proportionality of distribution among asnaf categories, which warrants further needs-based assessment in the Banyumas region.